2001
DOI: 10.1200/jco.2001.19.8.2247
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations in BRCA1 and BRCA2 in Breast-Ovarian Families From a Breast Cancer Risk Evaluation Clinic

Abstract: These results suggest that at least half of breast/ovarian families evaluated in a high-risk cancer evaluation clinic may have germline mutations in BRCA1 or BRCA2. Whether the remaining families have mutations in noncoding regions in BRCA1, mutations in other, as-yet-unidentified, low-penetrance susceptibility genes, or represent chance clustering remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 21 publications
5
45
1
2
Order By: Relevance
“…In keeping with what has been reported by others, 19,33 breast-ovarian cancer families were more likely to carry deleterious BRCA1/2 mutations than breast carcinoma-only families in our series. We also found good correlation between the likelihood of finding a deleterious mutation and genetic risk categories.…”
Section: Discussionsupporting
confidence: 79%
“…In keeping with what has been reported by others, 19,33 breast-ovarian cancer families were more likely to carry deleterious BRCA1/2 mutations than breast carcinoma-only families in our series. We also found good correlation between the likelihood of finding a deleterious mutation and genetic risk categories.…”
Section: Discussionsupporting
confidence: 79%
“…Mutations of the BRCA1 and BRCA2 genes are responsible for about 15 -40% of the breast cancer with familial aggregation and for the majority of hereditary ovarian cancer families. 1,2 Although initial data from the Linkage Consortium Study indicated a probability of 85% to develop breast cancer in a woman with BRCA gene mutation, 3,4 more recent studies suggest that the penetrance of BRCA1/2 mutations might be lower in non-highrisk families (Antoniou et al 5 and references therein). In the Italian population, the probability to develop a breast or an ovarian cancer at age 70 years was estimated to be 39 or 43%, respectively, for a BRCA1 mutation carrier and 44 and 15% for a BRCA2 mutation carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Key words: BRCA1, breast cancer, ovarian cancer. The Breast Cancer Linkage Consortium dataset indicates that the proportion of familial breast and ovarian cancers associated to BRCA1 or BRCA2 may be as high as 98% (Martin et al, 2001). Mutations in BRCA1 account for 45% of families with multiple cases of breast cancer and for at least 80% of families with early-onset breast and/or ovarian cancer (Miki et al, 1994).…”
mentioning
confidence: 99%